Arduino-based PLTS and PLN Hybrid Controller Design - Adelhard Beni Rehiara; Yanty Rumengan (Procedia of Engineering and Life Science, 2021)
Along with the technology that is starting to develop and the price is in the beginning to be affordable as well as good regulatory support from the government, solar power plant has become a new interest in today's society. The main problem of this power plant are complicated control system and quite expensive price. In this research, an Arduino-based hybrid controller has been developed to overcome this problem. The controller is designed to utilize power from power grid and the rooftop solar power. To increase system efficiency, design of the controller is based on the DC voltage for the lighting installation. Features available in this hybrid controller include overcurrent protection, two-stage battery voltage protection, automatic power transfer, timer for ON / OFF of outdoor lighting. The test results indicate that the designed controller achieves in accordance with the design requirements.